Giant parametric amplification of the nonlinear response in a single crystal of beryllium in a quantizing magnetic field - Tsindlekht, M.I.; Logoboy, N.; Egorov, V.S.; Kramer, R.B.G.; Jansen, A.G.M.; Joss, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The nonlinear response to an ac magnetic field with and without parametric pumping was studied experimentally on a rod-like beryllium single crystal at low temperatures in a quantizing magnetic field applied parallel to the hexagonal axis. At low temperatures (≤ 3 K) giant parametric amplification of the nonlinear response is observed in narrow windows near de Haas– van Alphen (dHvA) beating antinodes where the amplitude of the magnetic oscillations is maximal. This effect is of threshold character with respect to the amplitude of the dHvA oscillations and occurs as a result of a diamagnetic phase transition of a strongly correlated electron gas into nonuniform state with formation of Condon domain structure. It is shown that the nonuniform phase appears periodically in a magnetic field. The components of rectified signal field reproduce the envelope of H–T critical curves and can be used for reconstruction of diamagnetic phase diagrams.